Development of Amine-Functionalized MCM-41/Cellulose Acetate Mixed Matrix Membrane for CO2 Separation from CH4 - Babu, Dhanesh Kumar (IRC, 2017)
The removal of carbon dioxide (CO2) from methane (CH4) is crucial in industry processes such as natural gas purification to avoid the formation of acid in pipelines and to increase the energy content of natural gas. This project focuses on the development of Mixed Matrix Membrane (MMM) for gas separation. MMM is the combination of polymeric and inorganic fillers materials that has superior performance compared to its pure form. In this research work, cellulose acetate (CA) is chosen as a polymeric matrix, and MCM-41 is chosen as the filler. Furthermore, the MCM-41 is functionalized with primary, secondary, and tertiary amine functionalized groups and incorporated into CA for the fabrication of MMMs. The resultant membranes will be characterized by using Scanning Electron Microscope (SEM), Fourier Transform Infrared (FTIR), Energy Dispersive X-ray (EDX), Transmission Electron Microscopy (TEM) and Differential Scanning Calorimetry (DCS). SEM images show the distortion of cross section area of the CA membrane after it is incorporated with MCM-41 and functionalized MCM-41 particles. EDX shows the distribution of particles across the cross section of the membranes. When higher loading of particles is used sedimentation and agglomeration becomes sever in all functionalized MCM-41 particle MMMs. ATR-FTIR spectra shows the presence of functional groups of MCM-41 particles that were found in all MMMs. DSC results show increase in glass transition temperature Tg, as the membranes is incorporated with increasing order of amine functional group. Tg also increases when higher weight of the particle loading is used. For gas separation performance membranes were tested with pure CO2 and CH4 gases. Based on the results, AEPTMS-MCM-41-5/CA with 7.56 and 1.31 permeability of CO2 and CH4 respectively has the highest selectivity of CO2/CH4 which is 5.75.